Cytoprotective Effects of Organosulfur Compounds against Methimazole-Induced Toxicity in Isolated Rat Hepatocytes - Mohammad Ali Eghba; Hossein Babaei; Reza Heidari (Tabriz University of Medical Sciences, 2013)
Purpose: Methimazole is a drug widely used in hyperthyroidism. However, life-threatening hepatotoxicity has been associated with its clinical use. No protective agent has been found to be effective against methimazole-induced hepatotoxicity yet. Hence, the capacity of organosulfur compounds to protect rat hepatocytes against cytotoxic effects of methimazole and its proposed toxic metabolite, N-methylthiourea was evaluated. Methods: Hepatocytes were prepared by the method of collagenase enzyme perfusion via portal vein. Cells were treated with different concentrations of methimazole, N-methylthiourea, and organosulfur chemicals. Cell death, protein carbonylation, reactive oxygen species formation, lipid peroxidation, and mitochondrial depolarization were assessed as toxicity markers and the role of organosulfurs administration on them was investigated. Results: Methimazole caused a decrease in cellular glutathione content, mitochondrial membrane potential (ΔΨm) collapse, and protein carbonylation. In addition, an increase in reactive oxygen species (ROS) formation and lipid peroxidation was observed. Treating hepatocytes with N-methylthiourea caused a reduction in hepatocytes glutathione reservoirs and an elevation in carbonylated proteins, but no significant ROS formation, lipid peroxidation, or mitochondrial depolarization was observed. N-acetyl cysteine, allylmercaptan, and diallyldisulfide attenuated cell death and prevented ROS formation and lipid peroxidation caused by methimazole. Furthermore, organosulfur compounds diminished methimazole-induced mitochondrial damage and reduced the carbonylated proteins. In addition, these chemicals showed protective effects against cell death and protein carbonylation induced by methimazole metabolite. Conclusion: Organosulfur chemicals extend their protective effects against methimazole-induced toxicity by attenuating oxidative stress caused by this drug and preventing the adverse effects of methimazole and/or its metabolite (s) on subcellular components such as mitochondria.